Silencing of long-non-coding RNA ANCR suppresses the migration and invasion of osteosarcoma cells by activating the p38MAPK signalling pathway - Bo Liu; Hongyan Zhao; Lili Zhang; Xuefeng Shi (BMC Cancer, 2019)
Abstract Background Osteosarcoma (OS) is a malignancy of the bone that has no clearly identified prognostic factors for diagnosis. In this study, we evaluated the regulatory role of long non-coding RNA (lncRNA) ANCR on the migration and invasion of OS cells as well as the possible mechanism involving the p38MAPK signalling pathway. Methods ANCR expression was determined in OS tissues and OS cell lines (MG-63, S1353, U2OS, and UMR-106) by qRT-PCR. It was observed that ANCR was down-regulated in MG-63 and U2OS cells by 48 h of siRNA-ANCR (si-ANCR) transfection. The proliferation of transfected cells was determined using the CCK-8 and the EdU assays. The migration and invasion of transfected cells were determined by the Transwell assay. The expression of E-cadherin, N-cadherin, and phosphorylated p38MAPK (p-p38MAPK) proteins was determined by Western blot. In addition, combinatorial treatment of cells with si-ANCR + SB203580 (p38MAPK inhibitor) was performed to investigate the association between ANCR and MAPK signalling in OS cells. Results ANCR was up-regulated in OS cells and tissues. ANCR silencing significantly inhibited the proliferation rate, decreased the percentage of migration and invasion cells, down-regulated N-cadherin, and up-regulated E-cadherin and p-p38MAPK in MG-63 and U2OS cells. Inhibition of the p38MAPK signalling pathway (SB203580) in MG-63 and U2OS cells rescued si-ANCR-induced inhibition of cell migration and invasion. Conclusions Silencing of ANCR inhibited the migration and invasion of OS cells through activation of the p38MAPK signalling pathway.